Standing Height and its Estimation Utilizing Arm Spam and Foot Length Measurements in Dinaric Alps Population: A Systematic Review - Bojan Masanovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Several researches have reported the benefi ts of using various body parameters in predicting standing height, and arm span happened to be one of the most reliable ones in adults, while foot length measurement is the most reliable predictor during adolescent age. On the other hand, it is well-known that the tallness and body proportions are specifi c in the area covered by Dinaric Alps. Therefore, the purpose of this study was to investigate the potential relationship between arm span and foot length measurements and body height in Dinaric Alps population. The most visible electronic database (Google Scholar) was searched for original research articles available until April 2018. Then research fi ndings were summarized and relationship between arm span and foot length measurements and body height in Dinaric Alps population were identifi ed, as well as areas of future research were recommended. The assessment of body height using various anthropometric measures is very typical from the past centuries and it has been attempted to be studied by many researchers. However, it is important to underline that the arm span has been obtained as the most reliable body indicator for predicting the true height of an individual, while foot length was very close. However, the studies sampled with the populations which live at Dinaric Alps Mountains have specifi c estimates. Therefore, all the above-mentioned has confi rmed the necessity for developing separate body height models for each population on account of ethnic as well as regional diff erences.